Synthesis and swelling behavior of pH-responsive polyurethane poly(2-(diethylamino)ethyl methacrylate) hybrid materials - Pardini, Francisco (2013)
Polyurethane (PU)/poly[2-(diethylamino)ethyl methacrylate] hybrids, having a chemical bond between the PU and acrylic moieties and with different compositions, were prepared by the dispersion polymerization of 2-(diethylamino)ethyl methacrylate (DEA) in the presence of preformed PU chains with polymerizable terminal vinyl groups. The PU dispersion was synthesized accord- ing to a prepolymer mixing process by the polyaddition of isophorone diisocyanate, poly(propylene glycol), 2-hydroxyethyl methacry- late, and dimethylol propionic acid (DMPA). Then, it was dispersed in water by the prior neutralization of the carboxylic acid groups of DMPA with triethylamine, chain-extended with ethylenediamine. The effect of the DEA content on the swelling properties (water uptake and dynamic swelling degree) at different pHs and at 37C was determined. The samples were also characterized by Fourier transform infrared spectroscopy and modulated differential scanning calorimetry. The experimental results indicate a higher water uptake when the DEA content was increased on the hybrid materials and a significant change in the kinetics of swelling at pH 4 com- pared to those at pH 7. The water content of the hydrogels depended on the DEA content, and it was inversely proportional to the pH value. The pure PU film did not show important changes over the pH range examined in this study. The synthesized hybrids were useful as drug-delivery, pH-sensitive matrices.